The Pregnancy Outcome in Women with Polycystic Ovary Syndrome (KYAMC Journal, 2023)
Background: In women of reproductive age, polycystic ovarian syndrome (PCOS) is a prevalent endocrine condition. Menstrual irregularities (oligomenorrhea or amenorrhea), hirsutism, persistent acne, androgen-dependent alopecia, abdominal obesity, hypertension, and infertility are all clinical signs of PCOS.Objective: To assess the success of pregnancy in patients with polycystic ovary syndrome.Materials and Methods: This observational cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at Khwaja Yunus Ali Medical College and Hospital, Enayetpur, Sirajganj, Bangladesh from June 2020 to May 2022 for a period of two years. Women diagnosed with PCOS were willing to participate in our study were recruited from obstetrics Out patient Department (OPD) and antenatal ward of Department of Obstetrics and Gynaecology at Khwaja Yunus Ali Medical College and Hospital. After obtaining an informed consent from them, a detailed interview schedule containing socio- demographic details, menstrual/marital/ obstetric/past/personal/ family history was taken.Results: Concerning complications Preeclampsia was found in 5 (9.1%) of the PCOS patients but not in the non-PCOS patients. The differences in gestational age and mode of birth between the two groups were not statistically significant (p>0.05). Perinatal outcome: 21 (39.6%) PCOS patients were admitted to the Neonatal Intensive Care Unit (NICU), compared to 11 (20.0%) non-PCOS patients. Which of the two groups was statistically significant (p